Reading difficulties in preterm deaf children and deaf children with cochlear implants - Aiouadj, Sonia; Aloui, Rofaida (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
In our current study, we tried to address a very important topic in the educational process that occupied all researchers in the field of education, which is reading difficulties. We dealt with this difficulty in two groups, the first category represented deaf children who are equipped and the second category is deaf children who have cochlear implants, our study aimed to identify on the reading difficulties of the sample members and highlighting the most important reading-related problems that faced deaf children. We have used the clinical approach as a case study method for two “cases” suffering from hearing loss “deafness”, and their chronological age is (11 – 12) equipped, the first group is equipped with a hearing device and the second case is equipped with a cochlear implant device, and two tests were applied in our study, the first of which is the intelligence test "John Raven", which is the test of successive matrices (CPM), and the second is the reading test "the holiday text" L'allouette, which are adapted to the Algerian environment, and the study concluded that equipped deaf children and deaf children carrying cochlear implants have an average level of intelligence to below average, they suffer from reading difficulties represented in the presence of difficulties at the level of: visual discrimination, phonemic awareness, perception and auditory discrimination, and the effect of the deaf child's behavior on reading achievement.